Influence of the input-stage architecture on the in-laboratory test of a mid-infrared interferometer: application to the ALOHA up-conversion interferometer in the L band. Issue 1 (22nd December 2020) - Magri, Julie; Lehmann, Lucien; Grossard, Ludovic; Delage, Laurent; Reynaud, François; Chauvet, Mathieu; Bassignot, Florent; Krawczyk, Rodolphe; Le Duigou, Jean-Michel
ABSTRACT: In the framework of the Astronomical Light Optical Hybrid Analysis (ALOHA) laboratory mid-infrared (MIR) up-conversion fibred interferometer in the L band, we report on the influence of the input-stage architecture. Using an amplitude division set-up in the visible or near-infrared is a straightforward choice in most cases. In the MIR context, the results are slightly different and we show that a wavefront division set-up is needed. These in-laboratory principle experiments allow us to measure a reliable 88 per cent instrumental contrast with high flux and to obtain fringes from faint sources at 3.5 μ m with a spectral bandwith of 37 nm converted to 817 nm. An equivalent limiting L -band magnitude around 3.9, equivalent to 3.0 fW nm −1, could be demonstrated on 1 m class telescopes. This opens the possibility of planning future on-sky tests at the Center for High Angular Resolution Astronomy (CHARA) array and of predicting the performance attained.